ALTERATION EFFECTS OF VOLCANIC ASH IN SEAWATER: ANOMALOUS Y/HO RATIOS IN COASTAL WATERS OF THE CENTRAL MEDITERRANEAN SEA - Censi P.; Sprovieri M.; Larocca D.; Aricò P.; Ferla P.; Saiano F.; Mazzola S. (My University, 2007)
This paper presents the results of a study based on data collected during the oceanographic cruise ANSIC 2001 carried out in the Ionian Sea during the explosive activity of Mount Etna in the summer of 2001. Anomalous low values of Y/Ho ratios in seawater suggest extensive scavenging processes on the surfaces of smectitic alteration products, with Y and Ho fractionation controlled by the differences in their electronic configurations and behaviour during solution/surface complexation equilibria. These processes can also be traced through the presence of significant tetrad effects recorded in the chondrite-normalised Rare Earth Elements and Yttrium (YREEs) patterns of suspended particulate matter. This suggests that the preferential Y scavenging from seawater is due to the formation of inner-sphere complexes with OH- groups on montmorillonite crystal surfaces. The preliminary results of kinetic experiments of YREE released from volcanic ash to coexisting seawater, and the related effects on Y/Ho ratios and Ce anomalies, are consistent with the fractionation of Light Rare Earth Elements (LREEs) with respect to Heavy Rare Earth Elements (HREEs) observed in dissolved phase. They suggest a behaviour of Y similar to that reported for LREEs, particularly for Ce and Pr. © 2007 Elsevier Ltd. All rights reserved.